POSTPARTUM REHABILITATION OF PATIENTS THAT HAVE SUFFERED LOSS-SAVING SURGERY – METRORAPHY AND METROPLASTY - Umarova Nargiza Mirzoyevna (Scholar Express Journals, 2022)
Despite the favorable outcomes after metroplasty and metrorhaphy (secondary suturing), this surgical intervention should not be recommended for general widespread implementation. Given the complexity of the operation involving surgeons, preoperative intensive care for genital sepsis, a very complex and long stage of nursing and rehabilitation of this contingent of women, such surgical tactics can only be applied in the conditions of Obstetric complexes and Level 3 Perinatal Centers, as well as multidisciplinary clinics (clusters), with well trained medical staff.
Keywords: Metroplasty; caesarean; metrorhaphy; postpartum rehabilitation